Implementing effective trade remedy mechanisms : a critical analysis of Nigeria's Anti-Dumping and Countervailing Bill, 2010 - Soyeju, Olufemi Olugbemiga (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2014